Brief Research Report: Effect of Triiodothyronine on Hepatic Growth Hormone Receptor Expression in Primary Bovine Hepatocytes - Stiensmeier, Vera; Schmicke, Marion (Frontiers in Veterinary Science, 2022)
In previous studies triiodthyronine (T3) was found to be lower in cows with ketosis and an effect of T3 on Growth Hormone Receptor (GHR) expression is described e.g. in a human hepatoma cell line. Therefore, the aim of the present study was to test whether T3 affects GHR mRNA expression in a well-established bovine hepatocyte model. Hepatocytes were kept in a sandwich culture and stimulated for six days with constant (10 µg/ml) or decreasing (from 10 – 5 µg/ml) T3 concentrations, and GHR as well as IGF-1 mRNA expression was measured using RT-PCR. We could confirm in vitro that T3 has a stimulatory effect on GHR1A mRNA expression.